Incidence of febrile neutropenia during chemotherapy among patients with nonmyeloid cancer receiving filgrastim vs a filgrastim biosimilar - Schwartzberg LS; Lal LS; Balu S; Campbell K; Brekke L; Elliott C; Korrer S (ClinicoEconomics and Outcomes Research, 2018)
Lee S Schwartzberg,1,2 Lincy S Lal,3 Sanjeev Balu,4 Kim Campbell,4 Lee Brekke,3 Caitlin Elliott,3 Stephanie Korrer3 1West Cancer Center, Memphis, TN, USA; 2Division of Hematology and Oncology, University of Tennessee, Memphis, TN, USA; 3Health Economics and Outcomes Research, Optum, Eden Prairie, MN, USA; 4US Clinical Development and Medical Affairs, Sandoz Inc., Princeton, NJ, USA Background: Filgrastim and other granulocyte colony-stimulating factors are recommended to decrease febrile neutropenia (FN) incidence among patients with nonmyeloid cancers undergoing chemotherapy. Data comparing biosimilar filgrastim-sndz with reference filgrastim (filgrastim-ref) are limited outside of clinical trials in the US. Objective: To compare the incidence of FN across chemotherapy cycles 1–6 between patients treated with filgrastim-sndz vs filgrastim-ref. Materials and methods: This was a retrospective claims analysis of patients with nonmyeloid cancer enrolled in commercial or Medicare Advantage plans from March 2015 to June 2016 and receiving filgrastim-sndz or filgrastim-ref during ≥1 completed chemotherapy cycle. Patients undergoing hematopoietic stem cell transplantation, pregnant patients, and those with missing data were excluded. FN was identified using the diagnosis codes for neutropenia + fever, neutropenia + bacterial/fungal infection, and neutropenia + infection + fever. Equivalence testing for FN incidence at the cycle level across chemotherapy cycles 1–6 was conducted for filgrastim-sndz vs filgrastim-ref after adjusting for baseline characteristics using inverse probability of treatment weighting. Results were considered equivalent if the 90% CIs for between-cohort differences were within ±6.0%. Results: The analysis included 3,459 patients (162 filgrastim-sndz and 3,297 filgrastim-ref). Before weighting, the filgrastim-sndz cohort was younger than filgrastim-ref and had a higher proportion of men, a higher proportion with commercial insurance, and lower proportions with granulocyte colony-stimulating factor prophylaxis or metastatic cancer. After weighting, baseline characteristics were similar between cohorts. Adjusted FN incidence was equivalent for filgrastim-sndz vs filgrastim-ref, respectively: neutropenia + fever, 0.81% vs 0.61% (difference [90% CI]=0.20 [−0.57 to 1.56]); neutropenia + infection, 1.21% vs 1.33% (difference [90% CI]=−0.12 [−1.17 to 2.28]); neutropenia + infection + fever, 0.0% vs 0.14% (difference=–0.14; CI not calculated because filgrastim-sndz had 0 events). Conclusion: Filgrastim-sndz and filgrastim-ref are statistically equivalent for preventing FN across chemotherapy cycles 1–6 among patients with nonmyeloid cancer. Keywords: biosimilar pharmaceuticals, febrile neutropenia, filgrastim, granulocyte colony-stimulating factor, retrospective studies